2017
DOI: 10.1097/md.0000000000007604
|View full text |Cite
|
Sign up to set email alerts
|

Can patients with femoral neck fracture benefit from preoperative thromboprophylaxis?

Abstract: Background:The effectiveness of preoperative thromboprophylaxis remains obscure in patients with femoral neck fracture. The purpose of the current study was to investigate whether these patients benefit from preoperative thromboprophylaxis.Methods:In this prospective, randomized controlled trial, a total of 80 patients with femoral neck fracture were randomly assigned to receive either rivaroxaban or conservative treatment before surgery. For all patients, color Doppler ultrasound of both lower extremities was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…In femoral neck fractures, the incidence of DVT was reported to be up to 19.5%. 7 In our study, the incidence was higher than in other studies. The reasons include the following aspects.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In femoral neck fractures, the incidence of DVT was reported to be up to 19.5%. 7 In our study, the incidence was higher than in other studies. The reasons include the following aspects.…”
Section: Discussioncontrasting
confidence: 68%
“…As for femoral neck fractures, the incidence of DVT is reported to range from 2.6% 2 to 19.5%. 7 However, we consider the actual incidence of DVT after femoral neck fracture is underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…Within the hip fracture population, work has suggested that the risk of VTE is in keeping with the degree of comorbidity [ 25 ]. The literature also suggests that in order to avoid VTE, early surgery (within 48 h) and pharmacological (or in combination with mechanical) thromboprophylaxis is vital [ 26 , 27 ]. The incidence of asymptomatic VTE in hip fracture patients without thromboprophylaxis is between 42%–50% [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deep venous thrombosis (DVT) and pulmonary embolism (PE) are both important clinical manifestations of venous thromboembolism (VTE). Particularly, the DVT was found to be present in 19.5–32% of patients preoperatively [ 6 , 7 ] and up to 56% of patients postoperatively [ 7 ]. Furthermore, DVT is a major resource of PE [ 8 ].…”
Section: Introductionmentioning
confidence: 99%